Region-specific hippocampal atrophy is correlated with poor glycemic control in type 2 diabetes: a cross-sectional study - Cuiping Bao; Xuehuan Liu; Yiming Li; Jun Yang; Feng Wei; Yi Gong; Zhihui Ma; Jun Liu (Endocrine Journal)
To examine the association between prediabetes/type 2 diabetes mellitus (T2DM) and hippocampal subfields and to investigate the effects of glycemic control (HbA1c and FBG)/diabetes duration on the volume of hippocampal subfields in T2DM patients. This cross-sectional study included 268 participants from Tianjin Union Medical Center between August 2019 and July 2022. The participants were divided into three groups: T2DM, prediabetes and no diabetes. All participants underwent brain MRI examination on a 3T MRI scanner. FreeSurfer was performed to segment hippocampus automatically based on T1 MPRAGE images. The relationships between glycemic status/glycemic control/diabetes duration and hippocampal subfield volumes were estimated by multiple linear regression analysis/generalized additive modeling (GAM). Among all participants, 76 (28.36%) had prediabetes, and 96 (35.82%) had T2DM. In multi-adjusted linear regression models, those with prediabetes had a significantly lower volume of bilateral parasubiculum (βright = –5.540; βleft = –6.497). Those with diabetes had lower volume of parasubiculum (βleft = –7.868), presubiculum-head (βleft = –6.244) and fimbria (βleft = –7.187). We did not find relationship between diabetes duration and hippocampal subfield volumes. In stratified analysis, long duration with high FBG related with lower volume of right fimbria (βright = –15.583). Long duration with high HbA1c related with lower volume of presubiculum-head (βright = –19.693), subiculum-head (βright = –28.303), subiculum-body (βleft = –38.599), CA1-head (βright = –62.300, βleft = –47.922), CA1-body (βright = –19.043), CA4-body (βright = –14.392), GC-ML-DG-head (βright = –20.521), GC-ML-DG-body (βright = –16.293, βleft = –12.799), molecular_layer_HP-head (βright = –44.202, βleft = –26.071) and molecular_layer_HP-body, (βright = –31.368), hippocampal_tail (βleft = –80.073). Prediabetes related with lower bilateral parasubiculum volume, and T2DM related with lower left parasubiculum, presubiculum-head and fimbria. T2DM with chronic poor glycemic control had lower volume in multiple hippocampal subregions.